Comparative Study on Interphase Force Model of Gas-Liquid Two-Phase Bubbly Flow Based on OpenFOAM - Liu, Chang; Wu, Haochuang; Lu, Wei; Chen, Deqi; Pan, Junjie; Li, Zhenzhong; Feng, Jintao (Journal of Advanced Thermal Science Research, 2022)
It is essential to choose an appropriate interphase force model when studying gas-liquid two-phase bubbly flow by numerical calculation. Because of the complexity of gas-liquid interaction, researchers have developed many models, while there is still a lack of corresponding guidelines when selecting the combination of interphase force models. In the present study, taking the DEDALE experimental condition as the research object, the parameter distribution characteristics of void fraction and gas-liquid two-phase velocity under the experimental condition are simulated, and the calculation results of different interphase force models are analyzed and compared with the experimental results. The effects of different interphase force models on the local parameter distribution characteristics of the two phases are analyzed and discussed, and the optimal model combination under this experimental condition is obtained.